Myths and legends: the reality of rape offences reported to a UK police force - Waterhouse, Genevieve F.; Reynolds, Ali; Egan, Vincent (Elsevier España S.L., 2016)
Rape myths affect many aspects of the investigative and criminal justice systems. One such myth, the‘real rape’ myth, states that most rapes involve a stranger using a weapon attacking a woman violently atnight in an isolated, outdoor area, and that women sustain serious injuries from these attacks. The presentstudy examined how often actual offences reported to a central UK police force over a two year periodmatched the ‘real rape’ myth. Out of 400 cases of rape reported, not a single incident was found withall the characteristics of the ‘real rape’ myth. The few stranger rapes that occurred had a strong link tonight-time economy activities, such as the victim and offender both having visited pubs, bars, and clubs.By contrast, the majority of reported rape offences (280 cases, 70.7%) were committed by people knownto the victim (e.g., domestic and acquaintance rapes), occurred inside a residence, with most victimssustaining no physical injuries from the attack. The benefits of these naturalistic findings from the fieldfor educating people about the inaccuracy of rape myths are discussed.